Perbedaan Disiplin Belajar Siswa SMP Ditinjau dari Jenis Kelamin - Mandrisa, Azagia; Sano, Afrizal (Lembaga Yasin AlSys, 2024)
This research is motivated by the fact that there are still students who lack discipline in studying. One of the factors that influences learning discipline is gender. This research aims to: (1) describe the learning discipline of male students, (2) describe the learning discipline of female students and, (3) test whether there are significant differences in learning discipline between male and female students at SMP Negeri 32 Padang . This research used a comparative descriptive approach, with a sample of 276 students using proportional stratified random sampling techniques. The results showed that the study discipline of male students was in the high category (76.19%), the study discipline of female students was also in the high category (80.64%) and there were significant differences in study discipline between male and female students with The significance level is 0.000.